2008
DOI: 10.1136/sti.2008.031583
|View full text |Cite
|
Sign up to set email alerts
|

Situational predictors of sexual risk episodes among men with HIV who have sex with men

Abstract: Background Men with HIV who have sex with men (MSM) represent the largest group of people living with HIV/AIDS in the United States. It is important to understand the sexual risk-taking behaviours that may be linked to the transmission of HIV and other sexually transmitted infections in this population. Models of HIV risk that focus solely on personal factors have been demonstrated to be ineffective at explaining risk behaviour. Rather, in order to fully understand sexual risk-taking, it is important to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 9 publications
3
55
1
Order By: Relevance
“…The findings from this study match those of analyses of dyadic encounters that found significant associations between drug use and UAI in MSM [2,3,5,26,27], and stands in contrast to those studies which have not found a significant association [6,7]. Previous studies have been mixed as to the association between location of sex and [5,7,[28][29][30].…”
Section: Implications For Research and Practicesupporting
confidence: 85%
See 2 more Smart Citations
“…The findings from this study match those of analyses of dyadic encounters that found significant associations between drug use and UAI in MSM [2,3,5,26,27], and stands in contrast to those studies which have not found a significant association [6,7]. Previous studies have been mixed as to the association between location of sex and [5,7,[28][29][30].…”
Section: Implications For Research and Practicesupporting
confidence: 85%
“…Previous studies have been mixed as to the association between location of sex and [5,7,[28][29][30]. The nonsignificant associations between location of sex and sexual risk behaviour in this study continue the debate and extend findings to multipartner encounters specifically.…”
Section: Implications For Research and Practicecontrasting
confidence: 45%
See 1 more Smart Citation
“…Private sex parties may be an especially important type of GSE regarding HIV sexual risk among MSM [2,6,7,15]. Between 8 and 25% of MSM in various studies report having met recent male sex partners at private sex parties [6,16,17], and meeting sexual partners at sex parties has been associated with high-risk sexual behavior [6,7,9]. Bareback sex parties have been associated with particularly high-risk behaviors among MSM.…”
Section: Introductionmentioning
confidence: 96%
“…Environmental contexts, such as venues where men who have sex with men (MSM) meet sexual partners, may influence sexual behavior and HIV risk [1][2][3][4][5][6][7][8][9][10]. Group sex events (GSEs) have begun to receive attention as an emerging risk environment for transmission and acquisition of HIV and other sexually transmitted diseases (STDs) among MSM.…”
Section: Introductionmentioning
confidence: 99%